2015
DOI: 10.1371/journal.pone.0141334
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Proteins RPS11 and RPS20, Two Stress-Response Markers of Glioblastoma Stem Cells, Are Novel Predictors of Poor Prognosis in Glioblastoma Patients

Abstract: Glioblastoma stem cells (GSC) co-exhibiting a tumor-initiating capacity and a radio-chemoresistant phenotype, are a compelling cell model for explaining tumor recurrence. We have previously characterized patient-derived, treatment-resistant GSC clones (TRGC) that survived radiochemotherapy. Compared to glucose-dependent, treatment-sensitive GSC clones (TSGC), TRGC exhibited reduced glucose dependence that favor the fatty acid oxidation pathway as their energy source. Using comparative genome-wide transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 63 publications
(59 reference statements)
1
41
0
Order By: Relevance
“…One of the few canonical RPs we found to be differentially incorporated was RpS11 in the head 80S ribosomes. RpS11 phosphorylation, in humans, has been found to be linked to Parkinson’s disease [39] and higher levels of RpS11 correlate with poorer prognosis in glioblastoma patients [40]. Therefore, understanding RpS11 levels in Drosophila head could provide a mechanism of future exploration for dissecting the molecular mechanisms by which RP mutations result in human disease.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few canonical RPs we found to be differentially incorporated was RpS11 in the head 80S ribosomes. RpS11 phosphorylation, in humans, has been found to be linked to Parkinson’s disease [39] and higher levels of RpS11 correlate with poorer prognosis in glioblastoma patients [40]. Therefore, understanding RpS11 levels in Drosophila head could provide a mechanism of future exploration for dissecting the molecular mechanisms by which RP mutations result in human disease.…”
Section: Discussionmentioning
confidence: 99%
“…(Tian et al, 2015) Glioblastoma S11, S15a, S20 Upregulation Overexpression of S11 and S20 is associated with shorter patient survival. (Yao et al, 2015;Yong et al, 2015) Pancreatic cancer L15 Downregulation Low expression of L15 is associated with tumor progression and predicts poor overall survival. (Yan et al, 2015) Ovarian cancer L13a, L29 Upregulation Low level of S4X in human serous epithelial ovarian cancer is associated with poor prognosis.…”
Section: Rps As Potential Cancer Biomarkersmentioning
confidence: 99%
“…Of these GO terms, ribosomal, RNA, and ubiquitin related are among the pathways holding the highest statistical significance. Ribosomal proteins are most commonly known to be involved in protein synthesis but have also been shown to exert extraribosomal functions including immune signaling and development of various cell types as well as being implicated in various cancers including glioblastoma, gastrointestinal, prostate, and lung . In this study, expression levels of many genes, encoding ribosomal proteins (Rp), were found to be differentially regulated in both Tpm1.12‐ and Tpm2.1‐overexpressing cells including Rpl9, Rpl13, Rpl19, and Rpl22 .…”
Section: Resultsmentioning
confidence: 77%